Legal Resource Needs in Small States (Commonwealth Pacific Jurisdictions) - Barton, George P (Victoria University of Wellington Law Review, 1999)
This report by Dr Barton was the result of a survey of the legal resource needs of small Commonwealth states in the Pacific commissioned by the Commonwealth Secretariat in 1979. Dr Barton spent a month and a half visiting the 8 nation states between May and October of 1979. The terms of reference focussed on obtaining a factually based profile of the legal-constitutional needs of each state and are reflected in the various sections of the report. In particular, the terms of reference directed Dr Barton to "examine ways in which the special legal requirements of these jurisdictions may most effectively and efficiently be met bearing in mind the limited resources available and seeking to make maximum use of assistance which it might be possible to arrange from other institutions ifor example, from university law faculties) and in close collaboration with existing regional institutions in the Pacific". In response to this Dr Barton suggests, among other things, a regional legal unit to serve the area, a suggestion which still has relevance today. Although Dr Barton's ideas for a regional advice unit were never implemented it is significant that a Pacific Law Unit for training purposes was established in Vanuatu with Commonwealth Secretariat and New Zealand Government support and latterly a regional law school has been established in Vanuatu by the University of South Pacific. In particular his comment that "in newly independent territories the need for legislative texts that are both up-to-date and readily available is particularly urgent" found a response in Victoria University Law Faculty based legislation master lists (Samoa, Solomon Islands) and in consolidated collections for Cook Islands, Niue, Norfolk Island and Tokelau.